Potensial Fatty Oil Pollution from Restaurant Wastewater: Potensi Pencemaran Minyak Lemak Dari Air Limbah Rumah Makan - Virgian Nur Kharismasari Faradillah; Peni Pujiastuti (Jurnal Kimia dan Rekayasa, 2022)
Wastewater from community activities such as restaurants, with the characteristic number of parameters exceeding the quality standard of wastewater, which is not treated but is directly discharged into the receiving water body, will have the potential to cause environmental pollution. The source of waste generation comes from the use of soap in washing cutlery which will result in an increase in the pH of the wastewater, and the cooking process causes the presence of fatty oil waste. This study aims to determine the potential for water pollution from pH and fatty oil parameters in restaurant wastewater from three different categories in Karanganyar Regency. Laboratory descriptive research method. The test samples were taken in a time-composite manner at the outlets of fast food restaurants, traditional and coffee shops which were selected with the best-selling criteria. Determination of the potential for causing pollution is seen from the number of parameters compared to the quality standard of domestic wastewater according to Central Java Regional Regulation number 5 of 2012. The pH value is determined based on SNI 6989.11:2019, while the fat oil number is determined by the gravimetric method according to SNI 6989.10:2011. The results of the study showed that the pH value of the wastewater test samples from fast food restaurants was 7.5 – 7.82, traditional restaurants were 8.11 – 8.44, and coffee shops were 7.97-8.16. Fat oil figures show differences in the three test samples, fast food restaurant wastewater 92.67 mg/l, traditional restaurant 1,143 mg/l, and coffee 54.33 mg/l. Restaurant wastewater has a great potential to pollute the water environment on the fat oil parameters. Abstrak Air limbah dari kegiatan masyarakat seperti rumah makan, dengan karakteristik angka parameter melebihi baku mutu air limbah, yang tidak dilakukan proses pengolahan namun langsung dibuang ke badan air penerima, akan memiliki potensi menimbulkan pencemaran lingkungan. Sumber timbulan limbah berasal dari penggunaan sabun dalam pencucian alat makan akan mengakibatkan naiknya pH pada air limbah, dan proses memasak menyebabkan adanya limbah minyak lemak. Penelitian ini bertujuan untuk menentukan potensi pencemaran air dari parameter pH dan minyak lemak pada air limbah rumah makan dari tiga kategori yang berbeda di Kabupaten Karanganyar. Metode penelitian diskriptif laboratoris. Contoh uji diambil secara komposit waktu pada outlet rumah makan cepat saji, tradisional dan coffee shop yang dipilih dengan kriteria terlaris. Penentuan potensi menimbulkan pencemaran dilihat dari angka parameter yang dibandingkan dengan baku mutu air limbah domestik sesuai Perda Jateng nomor 5 tahun 2012. Angka pH ditentukan berdasarkan SNI 6989.11:2019, sedangkan angka minyak lemak ditentukan dengan metode gravimetri sesuai SNI 6989.10:2011. Hasil penelitian nilai  pH contoh uji air limbah rumah makan cepat saji sebesar 7,5 – 7,82, rumah makan tradisional 8,11 – 8,44 sebesar, dan coffee shop sebesar 7,97- 8,16. Angka minyak lemak menunjukkan perbedaan pada tiga contoh uji,  air limbah rumah makan cepat saji sebesar 92,67 mg/, rumah makan tradisional l,143 mg/l, dan coffee shop 54,33 mg/l. Air limbah rumah makan memiliki potensi besar menimbulkan pencemaran lingkungan air pada parameter minyak lemak.